2016
DOI: 10.1155/2016/2675937
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Biological Studies of a Piperidinyl Appended Dipicolylamine Ligand and Its Rhenium Tricarbonyl Complex as Potential Therapeutic Agents for Human Breast Cancer

Abstract: A novel ligand bearing a central piperidinyl sulfonamide group, N(SO2pip)dpa, and its corresponding Re tricarbonyl complex, [Re(CO)3(N(SO2pip)dpa)]+, have been synthesized in good yield. The methylene CH2 signal seen as a singlet (4.54 ppm) in a 1H NMR spectrum of the ligand in DMSO-d 6 appears as two doublets (5.39, 5.01 ppm) in a spectrum of the [Re(CO)3(N(SO2pip)dpa)]+ complex and confirms the presence of magnetically nonequivalent protons upon coordination to Re. Structural results revealed that the Re–N b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…3. Results and discussion 25 and 1.602 (9) A for N-methyltoluene-psulfonamide and 1.641 (2) A for N,N-dimethyltoluene-p-sulfonamide. 54 However, that has not been depicted by the shortening of S-N bond length in N(SO 2 (2-nap))dpa as that of the most common cases.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…3. Results and discussion 25 and 1.602 (9) A for N-methyltoluene-psulfonamide and 1.641 (2) A for N,N-dimethyltoluene-p-sulfonamide. 54 However, that has not been depicted by the shortening of S-N bond length in N(SO 2 (2-nap))dpa as that of the most common cases.…”
Section: Methodsmentioning
confidence: 95%
“…This C6-N2 bond distance (pyridyl N and methylene carbon) of bidentate [PtCl 2 (N(SO 2 pip)dpa)] (1.477 (4) A) complex is not signicantly different to that of tridentate [Re(CO) 3 (-N(SO 2 pip)dpa)] + (1.4615 (16) A) complex. 25 In [PtCl 2 (N(SO 2 (1-nap))dpa)], Pt1-N3 and Pt1-N1 (2.029 A, 2.027 A) bond distances are similar to Pt-N bond lengths in compounds of the type [PtL 2 X 2 ] where L ¼ aniline and X ¼ halides and nitrites, 58 illustrating that the interaction between For the [PtCl 2 (N(SO 2 pip)dpa)] complex, the structural data revealed that the S-O bond lengths (Table 2) are similar to that of S]O in SO 2 (1.43 A). 54 Since the O-S-O angle is as wide as to 121.56 (16) A and the other angles around sulfur atom are slightly smaller in the range of 106.10-108.17 A (Table 3) than the ideal tetrahedral angle (109.5 ), the sulfonyl moiety represents a distorted tetrahedral arrangement around the S atom.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no progress has been made towards efficient synthesis of coumarin-based dipic derivatives. Dipic ligands such as di(2-picolyl)amine (DPA) and N-substituted DPA derivatives have been investigated for anticancer activities against malignant cells [ 38 , 39 ]. Also, it is important to note that DPA exhibits co-ordination properties in metal complexes [ 40 ].…”
Section: Introductionmentioning
confidence: 99%